Pengaruh Anteseden Niat Rekomendasi Terhadap Pertumbuhan Net Promoter Score® Dan Pertumbuhan Pendapatan Perusahaan - Sandy Christian Listiono; Dudi Anandya (Conference In Business, Accounting, And Management (CBAM), 2012)
Business nowadays is growing rapidly and complex that makes competition moving faster (Fornell, 2007). Most company applied various method to measure customer satisfaction in order to monitor their performance (Anderson et al., 1994), which is according to Keiningham et al. (2008), it is not suitable enough. Reichheld (2003) argue that the measurement of customer loyalty were considered could give better picture to predict the income growth of a company. Such prediction could be clearly described by using the concept of Net Promoter Score® that based on the recommend intention of loyal customer.The research’s purpose is to analize the influence of recommend intention’s antecedent toward the growth of Net Promoter Score® and the growth of company’s revenue. The object of the research is PT X Laser Metalindo in Surabaya. While the respondent of the research are 100 companies which are the customer of PT X that is chosen with Stratified Random Sample method. The study findings suggest that the pathway of the recommend intention’s antecedent that proved significant was from the service quality, customer value, customer satisfaction and company reputation towards the growth of the Net Promoter Score®. But Reichheld’s theory related to the influence and correlation of the Net Promoter Score® on the revenue growth is not proven.Key words: recommend intention, Net Promoter Score®, revenue growth